In vivo Safety Evaluation of a Nigerian Polyherbal Mixture in Female Wistar Rats (Nigerian Journal of Physiological Sciences, 2019)
The present study evaluates the oral safety and oral toxicity reversibility of a Nigerian Polyherbal Mixture (NPM) in female Wistar rats. In this study, acute oral toxicity was conducted on 20 female Wistar rats using the limit dose test of Up-And-Down Procedure of the OECD Acute Oral Toxicity Testing 425 guidelines at 5000 mg/kg of NPM. Additionally, 40 female Wistar rats (120-150 g) were divided into 4 groups (n=10) and orally treated with 10ml/kg of distilled water, 82 mg/kg, 410 mg/kg and 2050 mg/kg of NPM, respectively, for 90 days. Five rats from each group were sacrificed while the remaining rats in each group were kept for another 14 days for oral toxicities reversibility test. Blood samples and vital organs were obtained for biochemical, hematological and histological changes. Results showed that acute oral toxicity testing of NPM caused no death in any of the three sequentially treated rats and its estimated LD50 value was greater than 5000 mg/kg. Chronic oral treatment with 82-2050 mg/kg NPM caused significant elevations in the serum urea and creatinine and full blood count parameters (except differential WBC counts). The elevated renal function parameters were corroborated by dose-related histological changes of renal tubular congestions. also caused profound thrombocytosis and histopathological changes of pulmonary interstitial widening and gastritis. In conclusion, NPM may not be considered safe for consumption on prolonged use and at a high dose due to its profound tendencies to cause pulmonary fibrosis, nephrotoxicity, gastritis and thrombo-embolism. However, all the biochemical and hematological but histopathological alterations induced by NPM were reversed 14 days after the treatment cessation.